The effect of online platform management and online interactions on donors’ engagement - Gálvez-Rodríguez, Mª del Mar; Herrada-Lores, Sara; Haro-de-Rosario, Arturo; Saraite-Sariene, Laura (Tec Empresarial, 2025)
This research examines the role of online platform management (websites and Social Networking Sites, SNS) and online interactions in donors’ engagement with nonprofit organisations (NPOs). To this end, we developed an index of the usage of websites and SNS for fostering donor engagement based on a sample of the top 100 NPOs in the United States, to then carry out a regression analysis. The main findings indicate that NPOs should improve the features of their websites and SNS to catch viewers’ attention and interest them in the information disclosed on online platforms to motivate them to support NPOs’ social mission. Results also show that NPOs that more effectively exploit their website and SNS design receive more private donations. The main type of online interaction that NPOs receive in response to posts is clicking actions. To a much lesser extent, online users opt to comment on posts. However, none of these online interactions are decisive for fostering private donations. This study contributes to the knowledge of websites and SNS best practices, providing financial support to NPOs. Likewise, it expands the understanding of users’ online participation as predictors of charitable giving behavior.